Common hepatic artery thrombosis after iatrogenic injury in pancreaticodudenectomy operation, unexpected course. (2016) - Hassan, Ramy; Ibraheem, Tameem; Taha, Ahmed; Fadel, Basher; Zidan, Ahmed
Highlights: Pancreatic resection is the only effective treatment with prolonged survival in operable pancreatic cancer and peri -ampullary cancer. We report here a case of common hepatic artery injury during pancreaticodudenectomy followed by complete thrombosis after its repair. Surprisingly liver enzymes and bilirubin start to improve in post operatively due to small hardly detected accessory left and middle hepatic artery. Abstract: Introduction: Pancreatic resection is the only effective treatment with prolonged survival in operable pancreatic cancer and peri -ampullary cancer; it is also a procedure of significant morbidity and complications. Vascular injury is one of the most serious intraoperative complications. Presentation of case: We report here a case of common hepatic artery injury during pancreaticodudenectomy followed by complete thrombosis after its repair. As common hepatic artery is the only arterial blood supply of the liver, acute liver failure and necrosis were the usual course. Surprisingly liver enzymes and bilirubin start to improve in post operatively due to small hardly detected accessory left and middle hepatic artery. Disscussion and conclusion: Although hepatic artery is the only arterial supply of the liver, occasionally small accessory arteries may give significant arterial blood supply. In such a situation liver enzymes act as surrogate markers to assess the sufficiency of this flow to the liver.